The global catalogue of microorganisms 10K type strain sequencing project: closing the genomic gaps for the validly published prokaryotic and fungi species. Issue 5 (22nd March 2018) - Wu, Linhuan; McCluskey, Kevin; Desmeth, Philippe; Liu, Shuangjiang; Hideaki, Sugawara; Yin, Ye; Moriya, Ohkuma; Itoh, Takashi; Kim, Cha Young; Lee, Jung-Sook; Zhou, Yuguang; Kawasaki, Hiroko; et al.
Abstract: Genomic information is essential for taxonomic, phylogenetic, and functional studies to comprehensively decipher the characteristics of microorganisms, to explore microbiomes through metagenomics, and to answer fundamental questions of nature and human life. However, large gaps remain in the available genomic sequencing information published for bacterial and archaeal species, and the gaps are even larger for fungal type strains. The Global Catalogue of Microorganisms (GCM) leads an internationally coordinated effort to sequence type strains and close gaps in the genomic maps of microorganisms. Hence, the GCM aims to promote research by deep-mining genomic data.